Vegetable Leafminer, Liriomyza sativae Blanchard (Insecta: Diptera: Agromyzidae): EENY255/IN507, 12/2001 - Capinera, John L. (EDIS, 2004)
This document is EENY-255, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: December 2001. EENY255/IN507: Vegetable Leafminer, Liriomyza sativae Blanchard (Insecta: Diptera: Agromyzidae) (ufl.edu)